Metabolic, adipose tissue and muscle predictors of obesity - Macdonald, Ian (Henry Stewart Talks, 2007)
Components of energy metabolism, Aerobic fuels, Energy and substrate balance, Partitioning of energy expenditure, Adipose tissue, Skeletal muscle, Metabolic disturbances in obesity